Evolusi Sharī'ah dan Wacana Fiqih - Abu Yasid (Islamica: Jurnal Studi Keislaman, 2010)
Sharī'ah has always been deemed as an integral part of Muslims life. As a binding and commanding divine law, Sharī'ah has in other words been internalized in the being and existence of Muslims through their obedience and regular practice. The question that this paper tries to answer is whether Sharī'ah is divine and transcendent, or is it evolving from being transcendent to becoming mere ideas and legal dictum of the ulama? To delve into this question the paper begins by saying that any legal formulation does stem from observation of social reality. Given the changing nature of social reality ?we argue- the product of legal extrapolation does exhibit some form of evolution. We further argue that so long as the heart of the divine law is human interest (maṣlaṣah) both worldly and heavenly, harī'ah cannot escape from the law of evolution considering that the interest of the vast span of humanity differs from one setting to another. That is why many jurists speak of the Maqasid al-Sharī'ah (the aims of harī'ah) implying that harī'ah does evolve given the multiplicity of these aims. Simply speaking, the paper is directed toward proving that harī'ah cannot be seen as stagnant and that it is subjected?like any other forms of knowledge?to the law of evolution.